Alexander Hamilton, revolutionary - Brockenbrough, Martha (Square Fish, 2019)
Author Brockenbrough offers an examination of Alexander Hamilton by presenting facts describing his political contributions to the founding of the United States, as well as his complex and sometimes scandalous personal life. Discusses his birth out of wedlock, teen years as an orphan, rise to power, untimely death, and legacy.